Seasonal variations of the semi-diurnal and diurnal tides in the MLT: multi-year MF radar observations from 2–70 N, modelled tides (GSWM, CMAM) - Hall, Chris; Manson, A.H.; Meek, C.; Hagan, M.; Koshyk, J.; Franke, S.; Fritts, D.; Hocking, W.; Igarashi, K.; MacDougall, J.; Riggin, D.; Vincent, R. (European Geophysical Society, 2002)
In an earlier paper (Manson et al., 1999a) tidal data (1990–1997) from six Medium Frequency Radars (MFR) were compared with the Global Scale Wave Model (GSWM, original 1995 version). The radars are located between the equator and high northern latitudes: Christmas Island (2° N), Hawaii (22° N), Urbana (40° N), London (43° N), Saskatoon (52° N) and Tromsø (70° N). Common harmonic analysis was applied, to ensure consistency of amplitudes and phases in the 75–95 km height range. For the diurnal tide, seasonal agreements between observations and model were excellent while for the semi-diurnal tide the seasonal transitions between clear solstitial states were less well captured by the model. Here the data set is increased by the addition of two locations in the Pacific-North American sector: Yamagawa 31° N, and Wakkanai 45° N. The GSWM model has undergone two additional developments (1998, 2000) to include an improved gravity wave (GW) stress parameterization, background winds from UARS systems and monthly tidal forcing for better characterization of seasonal change. The other model, the Canadian Middle Atmosphere Model (CMAM) which is a General Circulation Model, provides internally generated forcing (due to ozone and water vapour) for the tides. The two GSWM versions show distinct differences, with the 2000 version being either closer to, or further away from, the observations than the original 1995 version. CMAM provides results dependent upon the GW parameterization scheme inserted, but one of the schemes provides very useful tides, especially for the semi-diurnal component.